A New Potentiometric Sensor for the Selective Determination of Iron in Water Samples (International Journal of Scientific Research in Science and Technology, 2024)
A new PVC potentiometric sensor namely well discriminating to Fe (III) ions was processed by utilizing N, N’-bis (2-dimethoxybenzylidene) ethylenediamine as sheet carrier. The sensor exhibits a excellent-Nernstian slope of 19.5 mV per ten of something over a 7.3x 10-8- 1.0x 10-1 M aggregation range. It has a reaction opportunity of about 30 s and maybe secondhand for not completely 60 days outside some difference in potentials. The projected sensor disclosed very good discrimination for Fe3+ over a off-course assortment of different cations over a pH range 3.6–10. It was used to the direct perseverance of iron in water from faucet samples and, as a sign terminal, in potentiometric titrations of Fe3+ ion. The terminal was too favorably used to the adaptive evolution of iron in aqueous resolutions.